2021
DOI: 10.7759/cureus.19289
|View full text |Cite
|
Sign up to set email alerts
|

Stage Migration in Cervical Cancer Using the FIGO 2018 Staging System: A Retrospective Survival Analysis Using a Single-Institution Patient Cohort

Abstract: Introduction The International Federation of Gynecology and Obstetrics (FIGO) changed the staging system for cervical cancer in 2018 and formally allowed cross-sectional imaging for staging purposes. Stage IB is now divided into three substages based on tumor size (IB1 < 2 cm, IB2 2-4 cm and IB3 > 4 cm). The presence of lymph nodes in the pelvis or para-aortic region will upstage the patient to stage IIIC. The purpose of this study was to evaluate the extent of stage migration using the FIGO 2018 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…FIGO's 2018 staging system improved survival discrimination for stages I and IV patients, but great heterogeneity still existed among stage III patients based on the revised staging systems 32 . Similar findings were also reported by other treatment centers 33,34 . Additionally, three treatment‐related variables of surgery, RT, and CT were following closely behind as indicated in Figure 5.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…FIGO's 2018 staging system improved survival discrimination for stages I and IV patients, but great heterogeneity still existed among stage III patients based on the revised staging systems 32 . Similar findings were also reported by other treatment centers 33,34 . Additionally, three treatment‐related variables of surgery, RT, and CT were following closely behind as indicated in Figure 5.…”
Section: Discussionsupporting
confidence: 69%
“…32 Similar findings were also reported by other treatment centers. 33,34 Additionally, three treatmentrelated variables of surgery, RT, and CT were following closely behind as indicated in Figure 5. Previously, a large cohort, retrospective analysis in Japan also demonstrated that for patients with localized diseases, CC patients who underwent surgery-based treatment had a significant survival advantage over patients who had received RT, 35 which was similar to the current findings.…”
Section: F I G U R Ementioning
confidence: 96%
“…However, one idea worth considering is that LN status alone is insufficient for determining the clinical characteristics of Stage IIIC patients and may not be appropriate in the clinical setting. Some recent studies explored the rationality of Stage IIIC from the perspective of oncology prognosis and demonstrated that the survival rate of women with positive LN (Stage IIIC) disease was superior to that of those with Stage IIIA and IIIB tumors 5,8,18–21 …”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies explored the rationality of Stage IIIC from the perspective of oncology prognosis and demonstrated that the survival rate of women with positive LN (Stage IIIC) disease was superior to that of those with Stage IIIA and IIIB tumors. 5,8,[18][19][20][21] In several studies, the effect of local tumor size and extent on Stage IIIC outcomes was further explored according to the T classification of the TNM staging system. Consistent with our results, these studies indicated that primary cervical mass was an independent survival risk factor for patients with Stage IIIC disease.…”
Section: Discussionmentioning
confidence: 99%